ANALYSIS OF CONSUMER PERCEIVED QUALITY AND TRUST TO USAGE INTENTION OF QRIS AT COFFEESHOPS TRANSACTION IN MANADO - Junior Mamesah; Maryam Mangantar; Julio Lawren Rumokoy (Universitas Sam Ratulangi, 2023)
This study aims the influence of Perceived Quality and Perceived Trust on customers’ usage intention to use QRIS as a payment method at Coffee shop Manado. It is important to understand the factors that influence the use of QRIS in coffee shop transactions. Quantitative research the approach for testing objective theories by examining the relationship variables. The sample size consists of 100 respondent, aged 15-35 years, sampling method was used is non-probability sampling, using questionnaire as tool in collecting data. Multiple regression analysis is used for regression analysis that allows to analyze the relationship between dependent variable and two or more independent variables Perceived Quality has a positive influence on Usage Intention. Studies Perceived Trust has a positive influence on Usage Intention. Perceived Quality and Perceived Trust has a positive influence on Usage Intention. The results of this study have shown that Perceived Quality has a positive and significant effect on Usage intention. The results of this study have shown that Perceived Trust has a positive and significant effect on Usage intention. The results of this study have shown that Perceived Quality and Perceived Trust has a positive and significant effect on Usage intention. Keywords: perceived quality, perceived trust, usage intention